2020
DOI: 10.3390/ijms22010044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gut Metabolites and Microbiota in Healthy and Marginal Livers Submitted to Surgery

Abstract: Microbiota is defined as the collection of microorganisms within the gastrointestinal ecosystem. These microbes are strongly implicated in the stimulation of immune responses. An unbalanced microbiota, termed dysbiosis, is related to the development of several liver diseases. The bidirectional relationship between the gut, its microbiota and the liver is referred to as the gut–liver axis. The translocation of bacterial products from the intestine to the liver induces inflammation in different cell types such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 170 publications
1
19
0
Order By: Relevance
“…It has been widely reported that polysaccharides are the most abundant dietary components [ 61 ]. In the course of intestinal fermentation, polysaccharides can promote the growth of certain intestinal bacteria, thus changing the profile of the intestinal microbiota [ 62 ], which can contribute to the development of intestinal diseases and consequently have a negative effect on organs such as the liver [ 63 ], which may result in a reduction in the quality of liver grafts [ 64 ]. Of scientific and clinical interest, it has been clearly demonstrated that microbiota imbalance can provoke immune alterations and potentiate proinflammatory pathways [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that polysaccharides are the most abundant dietary components [ 61 ]. In the course of intestinal fermentation, polysaccharides can promote the growth of certain intestinal bacteria, thus changing the profile of the intestinal microbiota [ 62 ], which can contribute to the development of intestinal diseases and consequently have a negative effect on organs such as the liver [ 63 ], which may result in a reduction in the quality of liver grafts [ 64 ]. Of scientific and clinical interest, it has been clearly demonstrated that microbiota imbalance can provoke immune alterations and potentiate proinflammatory pathways [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing awareness of the adverse consequences of mucosal barrier failure in disorders not primarily originating in the gut, notably sepsis in critical illness [10] and HIV infection [12,13]. Furthermore, several disorders of the liver are accelerated by mi-crobial translocation [14], including alcoholic [15] and non-alcoholic fatty liver disease (NAFLD) [16].…”
Section: Introductionmentioning
confidence: 99%
“…BD negatively affects the hepatic function following transplantation [3,4], and livers with steatosis are more susceptible to ischemia-reperfusion (IR) injury, thus negatively affecting liver function and graft quality [5]. Therefore, many liver grafts are discarded, exacerbating the shortage of grafts [2,6]. In the surgery of hepatic resections, IR injury is currently performed to avoid excessive bleeding [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the surgery of hepatic resections, IR injury is currently performed to avoid excessive bleeding [7]. On the other hand, IR injury negatively affects regenerative capacity after partial hepatectomy (PH) [6], particularly in steatotic livers, resulting in the worst postoperative outcomes [6,8].…”
Section: Introductionmentioning
confidence: 99%